Conceptualizing Research Relationships to Enhance Broader Impacts at the University of New Mexico - Hannah Yohalem; Hannah R. Torres (The University of Alabama, 2024)
This paper focuses on enhancing researchers' ability to articulate and achieve societal impacts in their work using the ARIS Broad Impact (BI) Toolkit as a jumping off point. The authors conducted a survey of UNM researchers to understand their approach to societal impact and relationship-building in research projects. The key findings suggest that 1) researchers across disciplines and funding sources value societal impacts in their work; 2) most UNM researchers engage in collaborative relationships as part of their efforts to achieve broader societal impacts; and 3) while researchers feel confident in conceptualizing and carrying out activities related to broader societal impacts, they are less confident in writing BI statements for NSF proposals. Based on these findings, the authors recommend that research development professionals 1) emphasize the importance of finding meaning in research through its broader social impacts; 2) develop tools to support more intentional relationship-building in research projects; and 3) provide resources to help researchers translate their ideas into effective BI statements for proposals. The paper concludes by highlighting areas for further research, including student engagement, mentorship, and institutional questions about BI project development and evaluation. The authors argue that addressing these areas is crucial for enhancing the societal value and effectiveness of scholarly work, ultimately driving significant positive change through research.